An exploratory study of the economic potential of Philippine pili pulp oil from waste pulp - Catelo, Salvador P. (Journal of Economics, Management & Agricultural Development, 2016)
This paper aims to determine the status of the pili nut and pili pulp oil industry in the Philippines and the competitiveness of processing oil from pili (Canarium ovatum) waste pulp using the domestic resource cost approach. Results of analysis reveal that producing locally one kg of pili pulp oil costs Php 599. This is almost half the cost of importing olive oil - a close substitute - from Spain estimated at Php 1,310/kg. In terms of domestic resource cost, there exists comparative (economic) advantage in pili pulp oil production. With a domestic resource cost (DRC) of 0.72, pili pulp oil production in the Philippines is competitive and hence manifests considerable economic potential. It has both employment and income effects that any similar program on inclusive growth aims to generate. If all the pili pulp were processed and converted into pili pulp oil, a total of 262,000 metric tons worth about Php 212 million could have been generated in 2014.